Cytogenetic characterization of Eurysternus caribaeus (Coleoptera: Scarabaeidae): evidence of sex-autosome fusion and diploid number reduction prior to species dispersion - De Arcanjo, Amanda Paulino; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Silva, Ana Emilia Barros E.; De Moura, Rita de Cassia (Indian Acad Sciences, 2009)
Mitotic and meiotic chromosomes of several populations of Eurysternus caribaeus (Coleoptera: Scarabaeidae) were analysed through conventional staining, C-banding, base-specific fluorochromes, silver nitrate staining and fluorescent in situ hybridization (FISH). All specimens showed 2n = 8 in their karyotypes, with a neo-XY sex system (Y is a submetacentric and X a metacentric) and three pairs of submetacentric autosomes. The analysis of constitutive heterochromatin (CH) revealed small blocks located in the centromeric region of all chromosomes which do not present positive staining under the fluorochromes CMA3 and DAPI. Silver nitrate staining revealed that the nucleolar organizer region (NORs) is associated with the sex chromosomes. The FISH technique revealed that rDNA sites in the X and Y are different in size. Data from different populations indicate that the diploid number reduction (2n = 8) observed in E. caribaeus is established and presumably has preceded the dispersion of this species. Moreover, this reduction occasioned the translocation of rDNA sites to the sex chromosomes, X and Y, an uncommon pattern in Scarabaeidae that was observed for the first time by the FISH in this work.
Keywords: chromosome rearrangements; FISH; heterochromatin; meiosis; NORs